A combined salt–hard templating approach for synthesis of multi-modal porous carbons used for probing the simultaneous effects of porosity and electrode engineering on EDLC performance. (June 2015) - Bhandari, Nidhi; Dua, Rubal; Estevez, Luis; Sahore, Ritu; Giannelis, Emmanuel P.
Abstract: A new approach, based on a combination of salt and hard templating for producing multi-modal porous carbons is demonstrated. The hard template, silica nanoparticles, generate mesopores (∼22 nm), and in some cases borderline-macropores (∼64 nm), resulting in high pore volume (∼3.9 cm 3 /g) while the salt template, zinc chloride, generates borderline-mesopores (∼2 nm), thus imparting high surface area (∼2100 m 2 /g). The versatility of the proposed synthesis technique is demonstrated using: (i) dual salt templates with hard template resulting in magnetic, nanostructured-clay embedded (∼27% clay content), high surface area (∼1527 m 2 /g) bimodal carbons (∼2 and 70 nm pores), (ii) multiple hard templates with salt template resulting in tri-modal carbons (∼2, 12 and 28 nm pores), (iii) low temperature (450 °C) synthesis of bimodal carbons afforded by the presence of hygroscopic salt template, (iv) easy coupling with physical activation approaches. A selected set of thus synthesized carbons were used to evaluate, for the first time, the simultaneous effects of carbon porosity and pressure applied during electrode fabrication on EDLC performance. Electrode pressing was found to be more favorable for carbons containing hard-templated mesopores (∼87% capacitance retention at current density of 40 A/g) as compared to those without (∼54% capacitance retention).